Ipomoea noemana (Convolvulaceae) a new species from Ancash eastern slope in Peru - Jara, Enoc; Muñoz-Rodríguez, Pablo; Wood, John R. I.; Beltrán, Hamilton (Phytotaxa, 2020)
Ipomoea noemana, a new species of Ipomoea endemic to the Marañón river area in Peru and known from a single population, is described and illustrated. Its relationship with other species of Ipomoea is discussed in the light of its morphology and molecular analysis of DNA barcode sequences.